Internet, então, nem em sonhos!: um estudo interacionista sociodiscursivo sobre práticas de letramento digital no projeto de extensão Pescadores Online . - Garcia, Thais de Abreu (2013)
This study is situated in the field of Applied Linguistics, and it is characterized as qualitative action research. Our goal is to examine the literacy practices of a tutor in a community computing center, located in Barra de Mamanguape - a small fishing village in the north of the state of Paraíba, Brazil. The data was collected before and after the opening of the computing center in the village. The idea was to investigate how the literacy practices of the participant, especially the digital ones, would change in the course of the academic project named Pescadores Online, which was responsible for building the computing center, for providing broad band connection in Barra de Mamanguape, as well as for training the present tutors. In addition to investigating the participant's literacy practices, I decided to investigate his evaluation/interpretation regarding the academic project and related aspects. The research is based on the theories of the new literacy studies (STREET, 1984; BARTON et.al, 2000; KLEIMAN, 1995, 2005, 2007; OLIVEIRA & KLEIMAN, 2008), and on the theory of the Socio-discursive Interactionism (BRONCKART, 1999, 2006, 2008), with especial attention to the enunciative mechanisms, such as modalization. Our corpus consists of 2 questionnaires regarding the participant's literacy practices, a reading record, and 5 reflective reports. The procedures of collection and construction of our corpus occurred in two different phases: the first phase refers to the period before the computing center (during the time the tutors were being trainned), and the second one refers to the period after the opening of the computing center in Barra de Mamanguape (the action period itself). The results of this investigation show that the literacy practices of the participant increased in a significant way in the second phase, as compared to the first phase. The evaluations of the participant on the academic project show that, in the beginning, he was curious and suspicious, for he had never thought of having broad band connection in his village. As time went by, though, and when the actions started effectively in the community computing center, his evaluation and comments became more confident, and we could see a proud tutor who worked hard to get his community into the digital era. Thus, I came to the conclusion that this research not only helped us to understand the literacy practices and the cultural context of our participant, but it also played an important role in providing new guidelines for our practices as digital literacy agents.